Selected Cases of Bi-Area Contact for Cylindrical Elements - Czerniec, M.; Komorzycki, C.; Łucyszyn, R. (Engineering Transactions, 1998)
The paper presents a general solution to selected problems concerning the bi-area contact of cylindrical elements with small deviations from circular contour. Contact areas and pressure distribution were determined. In numerical calculations, three variants of joining elements in contact were taken into account. Influence of the ellipticity error on the contact area and the value of maximal contact pressures was presented in the figures.